The impact of student-curated exhibitions about socio-scientific issues on students’ perceptions regarding their competences and the science classes - Reis, Pedro (2020)
The IRRESISTIBLE Project (FP7, Grant 612367) had the aim of involving teachers, students, and the public in the discussion on Responsible Research and Innovation (RRI), promoting both the construction of knowledge on cutting-edge (and controversial) research topics and the discussion about the criteria that these research/innovation processes should respect in order to be considered as responsible. These criteria also represent a strong contribution to a more sustainable future for all. This quantitative research evaluates the impact of IRRESISTIBLE’s student-curated exhibitions–about the RRI dimensions of cutting-edge research topics (socio-scientific issues)–on students’ perceptions regarding their scientific competences and the science classes. A pre- and post-test questionnaire was developed, validated, and applied to students from 10 countries. The overall results of the statistical analysis indicate that students improved their perceptions regarding their competences in developing exhibitions in science classes as a way of creating awareness on topics relating to science, technology, and society. This activity reinforced students’ perceptions that in science classes they: (a) discuss current issues and how they impact their lives; (b) develop socially relevant projects; and (c) learn how to influence other citizens’ decisions about social issues related to science, technology, and the environment with the aim of assuring a more sustainable future.